Automation of the logatom intelligibility measurements in rooms - Brachmański, Stefan (Archives of Acoustics, 2007)
Speech intelligibility is one of basic quality parameters of speech transmission in rooms. The methods for assessment of speech quality fall into two classes: subjective and objective methods. This paper includes an overview of selected methods of subjective listening measurements (ACR – Absolute Category Rating, DCR – Degradation Category Rating, speech intelligibility) recommended by ITU-T, ISO and Polish Standard and the method of speech transmission quality evaluation called “modified intelligibility test with forced choice” (MITFC). The MIT-FC method provides fully automatized measurement of speech intelligibility in rooms. The experiments carried out in finding the relations between logatom intelligibility measured with traditional and theMIT-FC methods for the rooms have shown that there exists the multivalue and repetitive relation between them.